2017
DOI: 10.1371/journal.pone.0185068
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of adenylylated and deadenylylated forms of M. tuberculosis glutamine synthetase as a drug discovery platform

Abstract: Glutamine synthetase is a ubiquitous central enzyme in nitrogen metabolism that is controlled by up to four regulatory mechanisms, including adenylylation of some or all of the twelve subunits by adenylyl transferase. It is considered a potential therapeutic target for the treatment of tuberculosis, being essential for the growth of Mycobacterium tuberculosis, and is found extracellularly only in the pathogenic Mycobacterium strains. Human glutamine synthetase is not regulated by the adenylylation mechanism, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…It has been determined already that quaternary contacts are formed between the least conserved amino acid regions and show significant deviation from class to class 23 . The protein-protein interface analysis of eu-GSIII showed that the interface area is close to the value of ∼1930Å 2 , which is slightly weaker than 2262 Å 2 in pro-GSIII (Fig.5a) but it is still quite notable and higher or equal to previously reported values of ∼1552Å 2 and ∼1890Å 2 for intra-ring interfaces for GSI and GSII respectively 23 .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…It has been determined already that quaternary contacts are formed between the least conserved amino acid regions and show significant deviation from class to class 23 . The protein-protein interface analysis of eu-GSIII showed that the interface area is close to the value of ∼1930Å 2 , which is slightly weaker than 2262 Å 2 in pro-GSIII (Fig.5a) but it is still quite notable and higher or equal to previously reported values of ∼1552Å 2 and ∼1890Å 2 for intra-ring interfaces for GSI and GSII respectively 23 .…”
Section: Resultssupporting
confidence: 63%
“…Two datasets were collected: 646 image stacks from the 1.2 mg/ml GSIII stock and 445 image stacks from 0.6 mg/ml GSIII stock. Each image stack had 50 frames at a dosage of 2 e/Å 2 /frame and pixel size of 0.6509 Å. All data processing was performed in cryoSPARC v3.3.1 software 31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D and SI Appendix, Fig. S13 concentrations and ratios associated with the antimycobacterial activity of BDQ independent of substrate concentrations, demonstrating its intrinsic ability to directly sense and specifically respond, in part, to BDQ-mediated changes in AXP concentrations and energy charge in addition to its other well-known ATPdependent regulation by posttranslational modification (26,27). Moreover, isotopic labeling studies using 15 N-labeled glutamate after a nonlethal 3-d preincubation of Mtb with BDQ revealed an almost complete cessation of glutamine biosynthesis (Fig.…”
Section: Metabolic Linkage Analysis Of Bdq-associated Activity-specificmentioning
confidence: 99%
“…Recent studies aiming at mtGSI selective inhibition are exploring the ATP binding pocket, 48,67,70 the intermonomer interfaces, 40 or targeting the adenylated form of mtGSI. 71 GS inhibition in humans has been studied in animal models for neurodegenerative disorders. A recent review on this matter was published, where the use of MSO as a therapeutic agent is encouraged.…”
Section: Box 3 Gs Developments On the Pharmaceutical Industrymentioning
confidence: 99%